Updates in COVID-19 Related Lymphadenopathy - Frequent Deep Axillary Location and Possible Contralateral Involvement - Roxana, Pintican; Magdalena, Duma; Madalina, Szep; Calin, Schiau; Diana, Feier; Calin, Pop; Angelica, Chiorean (International Journal of Innovative Research in Medical Science, 2021)
Ipsilateral axillary lymphadenopathy related to COVID-19 vaccine was reported as a side effect and started to raise diagnostic dilemmas especially in oncology patients. Breast cancer patients are particularly prone to this benign pitfall that may result in unfortunate management changing or unnecessary biopsy, both causing additional emotional stress for the patients. We present three cases with axillary lymphadenopathy and one with axillary and bilateral supraclavicular lymphadenopathy, and focus on what haven’t been reported yet: the deep and more superior location for the axillary lymphadenopathy and the possibility of contralateral lymphadenopathy secondary to COVID-19 vaccine. Their implication in breast cancer management will also be briefly discussed.